Exploring important usability attributes of cellular phones based on customer needs: A case with turkish users - (:unkn) unknown (My University, 2005)
Usability of cellular phones have recently gained utmost importance in consideration of user comfort, user preference, product quality and marketing success. It is emphasized in literature that usability efforts should be based on customer needs. Furthermore, cultural differences between user groups play certain roles in shaping attitudes toward usability and behaviours in cellular phone use. In this study, important cellular phone usability attributes for Turkish users were explored. In-depth interviews were conducted for data gathering. Development of the interview was explained. Results of the in-depth interviews were discussed. This study is expected to contribute valuable findings to literature by empirically demonstrating the usability-related characteristics of Turkish cellular phone users.